2018
DOI: 10.1080/17461391.2018.1544278
|View full text |Cite
|
Sign up to set email alerts
|

Restricting short‐wavelength light in the evening to improve sleep in recreational athletes – A pilot study

Abstract: Sleep is crucial for recovery and skill acquisition in athletes. Paradoxically, athletes often encounter difficulties initiating and maintaining sleep, while having sufficient sleep opportunity. Blue (short-wavelength) light as emitted by electronic screens is considered a potential sleep thief, as it suppresses habitual melatonin secretion. The current study sought to investigate whether blocking short-wavelength light in the evening can improve sleep onset latency and potentially other sleep parameters among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Specifically, the human circadian pacemaker in the SCN is more sensitive to short or blue wavelength light (460 nm) than to long or red wavelength light (555 nm), as the short wavelength has been shown to suppress melatonin [24][25][26]. Intensity of the light also has a negative effect on sleep, but of lesser magnitude than wavelength of light [27]. Alternatively, limiting short-wavelength light exposure has been shown to significantly shorten sleep onset latency by 7 min, improve sleep quality, and increase alertness the following morning [28].…”
Section: Daylight Hoursmentioning
confidence: 99%
“…Specifically, the human circadian pacemaker in the SCN is more sensitive to short or blue wavelength light (460 nm) than to long or red wavelength light (555 nm), as the short wavelength has been shown to suppress melatonin [24][25][26]. Intensity of the light also has a negative effect on sleep, but of lesser magnitude than wavelength of light [27]. Alternatively, limiting short-wavelength light exposure has been shown to significantly shorten sleep onset latency by 7 min, improve sleep quality, and increase alertness the following morning [28].…”
Section: Daylight Hoursmentioning
confidence: 99%
“…Other studies found that using such devices before bedtime, for example for social interaction, may affect sleep quality but without necessarily reducing melatonin levels. 140,141 In recent years, several sets of metrics have been proposed for lighting that supports circadian entrainment. These are based on measures at eye level weighted against the spectral sensitivity of the melanopsin-containing ipRGCs.…”
Section: Getting the Right Light At The Right Timementioning
confidence: 99%
“…Other studies found that using such devices before bedtime, for example for social interaction, may affect sleep quality but without necessarily reducing melatonin levels. 140,141…”
Section: Minimising Detrimental Impacts From Home Lightingmentioning
confidence: 99%
“…Furthermore, while positive effects have been observed in clinical populations that suffered from pathology-related sleep problems (e.g. Alzheimer's disease, delayed/advanced sleep phase disorder, sleep onset insomnia), effects of light regulation on the sleep of young and healthy individuals such as athletes, remain largely unknown (cf., Knufinke, Fittkau-Koch, Møst, Kompier, & Nieuwenhuys, 2019).…”
Section: Introductionmentioning
confidence: 99%